2019
DOI: 10.29333/ejgm/94099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of instruction and implementation of a preventive urinary tract infection bundle on the incidence of catheter associated urinary tract infection in intensive care unit patients

Abstract: Background and Objective: Catheter Associated Urinary Tract infection (CAUTI) is one of the most prevalent hospital acquired infections which causes increased medical costs, hospital stay and mortality. Patients in critical care units are in a higher risk. The main purpose of the present study is the Identification of the effect of instruction and implementation of a preventive urinary tract infection bundle on the incidence of CAUTI. Materials and Methods: This was a before-after quasi-experimental study. 330… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…(31) . (2019) (34) . On the other hand, CAUTI was asymptomatic in critically ill patient that reported by Weiss, et al (2019) (35) Concerning blood chemistry.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…(31) . (2019) (34) . On the other hand, CAUTI was asymptomatic in critically ill patient that reported by Weiss, et al (2019) (35) Concerning blood chemistry.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…This is because most patients were unconscious and connected to MV which restricted their mobility. On the other hand, many studies reported that a UC is indicated for admitted patients in ICUs for fluid monitoring and management (Al meida et al, 2020;Dehghanrad et al, 2019;Fakih et al, 2010;B. Kim et al, 2017;Knill, Maduro, & Payne, 2018;Kuriyama et al, 2017;Sampathkumar, 2017).…”
Section: Section Ii: Comparing the Implementation Of The Cautis Bundl...mentioning
confidence: 99%
“…On the contrary, the studies were carried out in the developed countries such as the American studies (Clarke et al, 2013;Davis et al, 2018;Perrin et al, 2020;Tyson et al, 2018), European studies (Düzkaya, Bozkurt, Uysal, & Yakut, 2016;Letica-Kriegel et al, 2019), a Spainian study (Lerma et al, 2019), an Asian study (Dehghanrad et al, 2019), and another international study that was applied in 15 developing countries (Rosenthal et al, 2012) reported low CAUTIs rate. This disagreement may be due to adherence to CAUTIs guidelines and the availability of resources in the developed countries.…”
Section: Section Iii: Comparing the Cautis Rate Between The Studied G...mentioning
confidence: 99%
“…Gram-positive bacteria such as S. aureus and Gram-negative bacteria such as E. coli and P. aeruginosa can adhere and form biofilms on catheter device surfaces. The biofilm is a complicated structure population of microbes that produces an extracellular polymeric matrix that is adherent on a surface [1]. Urinary biofilms are documented to be of mixed microbial species [2], which makes their treatment and management challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of medical devices such as urinary catheters and stents is often reported to increase the risk of developing bladder infections [1,2]. Bacteria can colonize the outer surface of the catheter and lead to bacterial escape through the bladder and cause extraluminal infection.…”
Section: Introductionmentioning
confidence: 99%